Prediksi Pertumbuhan Lahan Terbangun pada Wilayah Selatan Kota Kendari Berbasis Cellular Automata - Westi Susi Aysa; Ihsan Ihsan; Isfa Sastrawati (Department of Urban and Regional Planning, Faculty of Engineering, University of Hasanuddin, 2015)
Land use change from non built up land into smaller plots is one phenomenon in urban areas that has relevance to a wide range of environmental issues that are vulnerable to disasters. Southern region of Kendari is a region whose development is quite rapid this is indicated by the number of land conversion non built up smaller plots resulting in several problems such as flooding that occurred. The way to anticipate by seeing growth trends of the land in the future. The purpose of this study is to identify the characteristics (direction and extent) of land growth during the last 10 years, identify the factors that influence the growth of non built up land and predict the growth of built up land 10 years to come. The analytical method used is the interpretation’s technique of satellite imagery (Landsat), spatial analysis using GIS and CA-Markov analysis with the help software idrisi selva 17. In this study the value for measuring the validity of the data and the results of prediction is using the kappa’s value. The study showed that the direction of growth of built up land during the last 10 years is leading to the south and east of the study site and widely increments of 50.18%. Factors affecting the growth of built up land that is the availability of public facilities, accessibility, government policies and the physical condition of the land (slope and topography). Growth forecast land up until 2024 that is experienced in increments of 1864.89 hectares or 21.07% with the addition of as many as 20.813 cells. The tendency towards the growth of land up to 2024 which led to the south, east and north of the location of the research with kappa’s value reaches 87% or classified as very good.